Video dialtone technology digital video over ADSL, HFC, FTTC, and ATM - Minoli, Daniel 1952- (McGraw-Hill, 1995)
This text provides a guide to the technology behind the competition to get on the information superhighway. It examines the technological solutions, looking at their long-term viability, current capabilities and impact on the race to win the market.